Trehalose rescues Alzheimer's disease phenotypes in APP/PS1 transgenic mice. (5th August 2013) - Du, Jing; Liang, Yu; Xu, Feng; Sun, Bing; Wang, Zhao
Abstract Objective Alzheimer's Disease (AD) is well characterized by the accumulated Aβ plaque in hippocampus and cerebral cortex concomitant with markedly reduced study and learning ability. Trehalose, a natural disaccharide, has been shown to have neural protective properties and exhibited therapeutic effects in animal models of several neural degenerative disorders. However, the effect of trehalose on AD pathology remains largely unknown. Methods In this study, we evaluated the effects of trehalose in APP/PS1 transgenic mice through behaviour tests and biochemical analyses. Key findings We found that the impaired cognitive and learning ability was improved and Aβ deposit in hippocampus was reduced. Conclusions These results suggested that trehalose could be a potential therapeutic drug for the treatment of AD.